Terapi Bermain Melipat dan Menempel Kertas Origami Pada Anak Usia Dini: Terapi Bermain Melipat dan Menempel Kertas Origami - Nurhayati, Ismi; Syaira, Renata; Maulana Nurona, Ridha; Lisa Lati, Lesa; Mohamad Sidik, Haris; Andriana, Bayu; Firmansyah, Andan (Yayasan Inspirasi El Burhani, 2024)
Introduction: The benefits of origami for young children are numerous. First, origami can help develop children's fine motor skills. The process of folding and gluing paper requires good hand-eye coordination, as well as fine motor skills. Second, origami can also help develop children's creativity and imagination. Children can create various shapes and objects just by folding paper. Method: This play therapy activity was carried out on Friday 17 November 2023 at the Al-Hidayah Ciomas Islamic Education Foundation, Panjalu sub-district. Participants in this activity were 24 preschool children and RA Al-Hidayah. The method used in this activity is divided into three stages, namely the preparation, implementation and final evaluation stages. In the preparation stage, we prepare tools, make time contracts, convey goals and topics, practice together, and prepare prizes for participants who have good work. Folded paper and hvs are used as media used by children to express their creativity. The instructions given to children are not limited, in the sense that children can express any ideas on hvs paper with origami tools as the main material. The goal is for students to have high thinking and creativity in creating creations using origami paper. Finally, in the evaluation stage, the staff reviews and assesses the children's work on how they draw using origami paper as the main basic material. Result: Playing activities for children were carried out on Friday 17 November 2023 at the Al-Hidayah Ciomas Islamic Education Foundation, Panjalu sub-district, this activity was attended by 29 children as participants. It is known that the implementation of play activities for children runs smoothly. Which was opened by the event section and continued by other implementing sections until the stage of implementing therapy for participants. And continued with evaluation, closing and documentation.Conclusion: Play therapy through origami, the Japanese art of paper folding, is an effective method for early childhood development. It helps in developing fine motor skills, creativity, imagination, and focus.